Distributed Power Allocation for Femtocell Networks Subject to Macrocell SINR Balancing - Cho, In-Sop; Baek, Seung Jun (IEEE communications letters, 2016)
We consider the power allocation for the two-tier heterogeneous network where a macrocell (MC) coexists with multiple femtocells (FCs). Each FC aims to maximize the weighted sum-rate of its users subject to MC signal-to-inter-ference-plus-noise ratio (SINR) balancing, which means that a prescribed SINR is guaranteed to MC users. We formulate a noncooperative game which captures bidirectional cross-tier interference. We develop a fully decentralized algorithm, and derive a sufficient condition for its convergence to a unique equilibrium.